2020
DOI: 10.1017/s0142716420000181
|View full text |Cite
|
Sign up to set email alerts
|

Reading minds in motion: Mouse tracking reveals transposed-character effects in Chinese compound word recognition

Abstract: This study investigated the development of character transposition effects during Chinese compound word recognition via computer mouse movements instead of the conventional key presses. Empirical evidence to reveal the impacts of vocabulary knowledge, grade level, and whole word frequency on Chinese transposed-character effect is lacking. In the present study, we measured the transposed-character effect in two groups of Taiwanese children (second and fourth graders) in a mouse-tracking lexical-decision task in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…In the present study, we used the mouse-tracking spoken word paradigm to examine whether bilingual listeners employ different phonological units depending on the language used in spoken word recognition. Over the past decade, mouse-tracking literature has suggested that hand movement trajectories recorded via a computer mouse in a wide range of linguistic tasks (e.g., lexical decision or spoken word recognition tasks) have provided insights into the temporally and spatially dynamic lexical activation and competition of written and spoken word recognition in monolingual and bilingual readers and listeners (e.g., Barca & Pezzulo, 2015; Lin & Lin, 2016, Lin et al, 2015, 2020; for written word recognition; see also Incera et al, 2020; Spivey et al, 2005; Zhao et al, 2011; for spoken word recognition). If the language-specific hypothesis of phonological units for bilingual listeners is the case, we should observe different levels of phonological competition when listeners process syllabic versus phonemic information during spoken word recognition in different languages (e.g., Chinese vs. English).…”
Section: The Subsyllable and Syllable As Phonological Units In Englis...mentioning
confidence: 99%
“…In the present study, we used the mouse-tracking spoken word paradigm to examine whether bilingual listeners employ different phonological units depending on the language used in spoken word recognition. Over the past decade, mouse-tracking literature has suggested that hand movement trajectories recorded via a computer mouse in a wide range of linguistic tasks (e.g., lexical decision or spoken word recognition tasks) have provided insights into the temporally and spatially dynamic lexical activation and competition of written and spoken word recognition in monolingual and bilingual readers and listeners (e.g., Barca & Pezzulo, 2015; Lin & Lin, 2016, Lin et al, 2015, 2020; for written word recognition; see also Incera et al, 2020; Spivey et al, 2005; Zhao et al, 2011; for spoken word recognition). If the language-specific hypothesis of phonological units for bilingual listeners is the case, we should observe different levels of phonological competition when listeners process syllabic versus phonemic information during spoken word recognition in different languages (e.g., Chinese vs. English).…”
Section: The Subsyllable and Syllable As Phonological Units In Englis...mentioning
confidence: 99%